2012
DOI: 10.5796/electrochemistry.80.720
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Coating of Si Thin Flakes and Negative Electrode Properties in Lithium-Ion Batteries

Abstract: To reduce the high irreversible capacity (Q irr ) of Si thin flake (Si-LP) negative electrode, carbon-coated Si-LPs were prepared using citric acid as a precursor and their charge/discharge properties were investigated as negative electrodes in lithium-ion batteries. The carbon-coated powder was homogeneously coated with a thin carbon layer (8-10 and 6-8 nm in thickness for Si-LPs heat-treated at 600 and 700°C, respectively, 14 wt% for each). The irreversible capacity Q irr was successfully reduced to about a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 22 publications
1
9
0
Order By: Relevance
“…The broad peaks indicate that the SNS are either nanosized or amorphous, which is consistent with the Si thin flake prepared by a physical vapor Nano Res. deposition (PVD) method by Okubo [27]. In this work, SNS is amorphous, which is further confirmed by Raman spectra (Fig.…”
Section: Resultssupporting
confidence: 84%
See 2 more Smart Citations
“…The broad peaks indicate that the SNS are either nanosized or amorphous, which is consistent with the Si thin flake prepared by a physical vapor Nano Res. deposition (PVD) method by Okubo [27]. In this work, SNS is amorphous, which is further confirmed by Raman spectra (Fig.…”
Section: Resultssupporting
confidence: 84%
“…Figures 2(c) and 2(d) show the SEM images of HO-SNS-W, as a typical example, after removal of Sn nanoparticles. Different from the previous SNS [27,34], which are completely planar in structure and easily stackable with one another, the peapod-like SNS shows a corrugated morphology with abundant void spaces. Furthermore, almost every single nanosheet is split into two or more thinner ones.…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…31 A carbon source, e.g. citric acid, was impregnated in Si-LP powder, and fired at 600, 700, and 800°C to coat the Si-LP powder with thin carbon layer.…”
Section: Large Irreversible Capacitymentioning
confidence: 99%
“…In the previous study, we demonstrated that the Si-CAP cell was improved by using additives, such as vinylene carbonate (VC) and fluoroethylene carbonate (FEC), and vacuum pressure impregnation (VPI) treatment during the Li pre-doping step. 15 The treatments effectively promoted preferred solid-electrolyte interface (SEI) film formation on the surface of the Si nanoparticles and homogeneous Li predoping into its bulk, which suppressed rapidly fading capacity by electrolyte decomposition 18,19 and a large volume change of Si. [20][21][22] In addition to the Li pre-doping technique, the limitation of Si NE capacity by that of the AC positive electrode (PE) in the hybrid capacitor system was also able to extend the cycle life of the Si-CAP; however, the effects on the charge/discharge properties of Si-CAP were only reported for short cycle periods (up to 50 cycles).…”
Section: Introductionmentioning
confidence: 99%